2014
DOI: 10.4244/eijv9i12a241
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparison of everolimus-eluting stents with sirolimus- and paclitaxel-eluting stents for percutaneous coronary intervention of saphenous vein grafts

Abstract: Aims: Newer-generation everolimus-eluting stents (EES) have been shown to improve clinical outcomes compared with early-generation sirolimus-eluting (SES) and paclitaxel-eluting stents (PES) in patients undergoing percutaneous coronary intervention (PCI). Whether this benefit is maintained among patients with saphenous vein graft (SVG) disease remains controversial. Methods and results:We assessed cumulative incidence rates (CIR) per 100 patient years after inverse probability of treatment weighting to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
(21 reference statements)
3
3
0
Order By: Relevance
“…Interestingly, no difference in mortality was reported in randomized controlled trials in the sensitivity analysis ( 20 ). A further study investigating newer generation DES reveals no significant difference as compared to early-generation stents over a follow-up period of four years ( 21 ), data consistent with our study where no difference between older and newer generation DES was seen.…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, no difference in mortality was reported in randomized controlled trials in the sensitivity analysis ( 20 ). A further study investigating newer generation DES reveals no significant difference as compared to early-generation stents over a follow-up period of four years ( 21 ), data consistent with our study where no difference between older and newer generation DES was seen.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover the "non-additional advantage" of the second-generation DES in SVGs PCI is supported by long-term results, albeit coming from retrospective studies. In a series of 12,339 patients with SVGs lesions newer-generation everolimus-eluting stents (EES) showed similar safety and efficacy to early-generation SES and PES during long-term follow-up to four years (22). Similar results have been provided by Pokala and colleagues in a comparison between first-generation SES and PES and second-generation EES and zotarolimus-eluting stents (ZES) at two years follow-up (23).…”
supporting
confidence: 55%
“…This result suggested that long‐term biocompatibility remained uncertain, even with the safest and most effective DESs in current use. Most clinical studies revealed that patients treated with current‐generation DESs uniformly experienced late target revascularization in ≈2% of cases . It could be concluded that the existence of polymer may have been responsible for the development of neoatherosclerosis, and thus biodegradable polymer‐based DESs would be expected to reduce the incidence of neoatherosclerosis.…”
Section: Introductionmentioning
confidence: 99%